The Influence of Students’ Physical Activity on the Use of Information Technology - Franzhardi, Didi; Hamzah, Syukri (Jurnal Basicedu, 2022)
Physical activity is very important for human health in carrying out daily activities. Activity lack of movement caused by too often playing online and offline games, internet, watching television too much will lead to the risk of obesity. A person's obesity is considered a risk factor for various diseases, such as diabetes, heart, hypertension and many others. One of the efforts that are considered to reduce the risk of obesity is to increase physical activity. Physical activity is not only limited to sports-specific activities, but also other activities that require physical labor, such as sweeping, mopping, washing, walking, dancing, painting, hoeing, walking and so on. This research aims to find out if there is an influence and how much information technology users have on the physical activity of students in SMK Negeri 5 Kota Bengkulu. This study is a non-experimental study. The subjects in this study were students of class X SMK Negeri 5 Kota Bengkulu by using a random sampling cluster consisting of 16 classes with a total of 558 students who were categorized as 72 male students and 486 female students. And from the results of the random sampling cluster obtained 5 classes with a total sample of 150 students. From the results of the calculation of statistics can conclude that there is no significant influence between the use of information technology on the physical activity of students. Because the data tests performed showed that the calculated r was smaller than the r tabelrhitung (-.717) > rtabel (0.197).